Pavement Performance Evaluation Using the Provincial and Kabupaten Road Management System (PKRMS) Method on the Parengan–Lakardowo Road Section, Mojokerto Regency - Miftakul Huda; Nurani Hartatik (Asosiasi Dosen Muda Indonesia, 2026)
Road infrastructure plays a vital role in supporting socio-economic mobility, yet its performance often decreases due to overloaded traffic, inadequate drainage, and limited maintenance. The Parengan–Lakardowo Road Section in Mojokerto Regency, with a total length of 5.182 km, currently experiences significant pavement deterioration that affects driving comfort and road safety. Objective: This study aims to evaluate the pavement performance of the Parengan–Lakardowo Road Section using the Provincial and Kabupaten Road Management System (PKRMS) to determine road conditions and formulate appropriate maintenance recommendations. Method: This research employed a quantitative descriptive method. Primary data were collected through field surveys, visual pavement condition assessment, damage measurement, and road inventory recording. The collected data were processed and analyzed using the PKRMS method to classify road conditions and identify maintenance priorities. Findings: The results show that the road condition varies across segments. Good condition was identified at STA 0+000–0+200, STA 0+600–1+000, STA 1+600–2+000, and STA 4+400–5+182. Lightly damaged condition was found at STA 0+200–0+600, while severely damaged condition dominated STA 1+000–1+600 and STA 2+000–4+400. The dominant pavement distresses include potholes, longitudinal cracking, alligator cracking, ravelling, and rutting. Implications: The findings indicate that severely damaged segments require structural treatment through pavement reconstruction, supported by drainage system improvement to prevent recurring deterioration and maintain pavement service life. The study also demonstrates the importance of integrated road condition evaluation for supporting sustainable road maintenance planning. Originality/Value: The originality of this study lies in the application of PKRMS for integrated pavement condition evaluation, stripmap-based condition mapping, and data-driven maintenance prioritization on a district road section in Mojokerto Regency.